A COMPREHENSIVE APPROACH TO CULTIVATING APPLIED TALENTS IN LOCAL UNDERGRADUATE UNIVERSITIES - Minghua, Dr. Li (Top Educational Review Journal (TERJ), 2023)
This study focuses on the imperative need to strengthen the cultivation of high-quality technical talents in local undergraduate universities, particularly in the context of transforming them into applied universities. These institutions play a pivotal role in the industrial transformation of old industrial bases and the cultivation of scarce talents essential for the revitalization of Northeast China. To achieve this, local undergraduate universities must embrace a central focus on talent development and adopt a strategy that involves establishing open enterprise practice teaching bases. This research explores the multifaceted connotation of enterprise practice teaching bases, emphasizing their role in integrating and enhancing collaboration between academic institutions and industries in terms of personnel training objectives, professional curricula, and practical teaching systems. The Ministry of Education’s "Guiding Opinions on Guiding Some Local Ordinary Undergraduate Universities to Transform into Application-oriented Universities" is a significant reference point, outlining the essential aspects of deepening reforms in talent training programs and curriculum systems. The document underscores the importance of innovative approaches in the training of application-oriented talents, the establishment of professional systems closely aligned with industrial and innovation chains, and the reinforcement of experimental practice bases.